A feasibility study on Balarbhita for advancing rural electrification with a solar—Micro-hydro hybrid system - Kanna, R. Rajesh; Singh, R. Raja (Frontiers in Energy Research, 2022)
The article analyzes the techno-economic feasibility of a village in the Indian state of Assam and designs a framework for a rural hybrid energy system. Through an extensive resource evaluation, techno-economic feasibility analysis and system size optimization are carried out using HOMER Pro software. Batteries are being used as a form of energy storage in the community power system, which is based on solar PV and micro-hydro as its principal energy sources. Macro-economic variables and resource variation have been considered in sensitivity analysis to ensure the robustness and commercial viability of the proposed hybrid energy systems. A reliable and economical design can provide 279861 kWh of electricity for the village at a modest cost of energy (COE) of 0.0953/kWh using 118 kW of solar power, 11 kW of hydropower, and 261 kWh of battery storage. Furthermore, solar energy systems account for about 62.5 percent, while micro-hydro turbines account for 37.5 percent. In addition, the suggested system does not pollute the local environment caused by carbon emissions. Most importantly, this hybrid energy system is capable of providing 24/7 continuous electricity to the site under consideration.